2006
DOI: 10.1111/j.1778-428x.2006.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Red cell salvage in orthopedic surgery

Abstract: SUMMARY The increasing number of surgical procedures has raised the demand for allogeneic blood to a level that often exceeds supply. Moreover, 10% of all transfusions are given in the orthopedic surgery setting, requiring the avoidance of liberal transfusion criteria to further reduce the risk of infection and other complications. As a result, a series of blood‐conservation measures have been developed. In this article, we review the use of autologous transfusion in orthopedic surgery, with a special focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…11 However, we found that the amount of PFHb reinfused with the washed salvaged product was identical to that of the unwashed system. Muñoz and colleagues 12 have previously reported a free Hb washout of 96% with the washed device employed in this study. While this washout percentage is impressive, it does not specify the maximum amount of PFHb that will be returned to the recipient since the residual amount of PFHb depends on the amount of PFHb that is present before washing.…”
Section: Discussionmentioning
confidence: 58%
“…11 However, we found that the amount of PFHb reinfused with the washed salvaged product was identical to that of the unwashed system. Muñoz and colleagues 12 have previously reported a free Hb washout of 96% with the washed device employed in this study. While this washout percentage is impressive, it does not specify the maximum amount of PFHb that will be returned to the recipient since the residual amount of PFHb depends on the amount of PFHb that is present before washing.…”
Section: Discussionmentioning
confidence: 58%
“…PABD increased from 15 123 units in 1994 to 24 390 units in 2004, with fluctuations between years (Table 1). The commonest area of application of PABD was orthopaedic surgery procedures where 80% of the collected PABD units were actually transfused [3]. When expressed as percentage of ABD, there was a discrete rise in PABD between 1994 and 1997.…”
Section: Allogeneic and Autologous Blood Collection In Spain 1994–2004mentioning
confidence: 99%
“…We found that postoperatively collected unwashed filtered shed blood after orthopaedic is safe and effective in reducing allogeneic blood transfusion requirements [2]. We retransfuse drained blood if a minimum of 400 ml are collected within the first six postoperative hours, and up to a maximum of 1000–1200 ml.…”
Section: Questions 2 and 8 Indications And Effectivenessmentioning
confidence: 99%
“…However, the contribution of unwashed filtered shed blood return to allogeneic blood transfusion reduction decreases if a transfusion protocol is adopted. From these data it can be inferred that a transfusion protocol does in itself reduce by 25–30% the relative risk for allogeneic blood transfusion and, therefore, it must be the first strategy to include in a blood saving program [2].…”
Section: Questions 2 and 8 Indications And Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation